Terpaparnya Paham Radikalisme pada Mahasiswa dan Implikasinya Terhadap Ketahanan Nasional - Nuryadi, Muhammad Hendri; Widiatmaka, Pipit (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aims to describe students as the main targets for radicalism, the implications of exposure to radicalism to students for national security, as well as strategies to deal with radicalism in higher education. This study uses a qualitative approach and a literature study research method. The data collection technique used is a documentation study. The data obtained were analyzed using heurmanic techniques. The results of the study show that students are the main target for radical groups because they have idealism, are critical, innovative, have a fighting spirit, and are easily influenced by new things. Exposure to radicalism in students has implications for weakening national security in Indonesia which affects several aspects of people's lives, namely ideology, politics, economics, socio-cultural life, and defence and security. Pancasila Education Course and Citizenship Education as a vehicle for deradicalization which is a strategy for tackling radicalism in tertiary institutions.